PENGARUH CASH RATIO,ROA,ASSET GROWTH,DAN LEVERAGE TERHADAP DIVIDEND PAYOUT RATIO PADA PERUSAHAAN KONSUMSI YANG TERDAFTAR DI INDONESIAN STOCK EXCHANGETAHUN 2017-2019PENGARUH CASH RATIO,ROA,ASSET GROWTH, DAN LEVERAGE TERHADAP DIVIDEND PAYOUT RATIO PADA PERUSAHAAN KONSUMSI YANG TERDAFTAR DI INDONESIAN STOCK EXCHANGE TAHUN 2017-2019 - saimin, Yusnita Sari (Akuntansi Prima, 2020)
The objective of the study is to test and analyze the effects of Cash Ratio, Roa, Asset Growth and Leverage on Dividend Payout Ratio in the Company Consumption, which is recorded on the Indonesian Stock Exchange 2017-2019, Samples used are 19 Companies that are listed in the consumption company sector, in the sample selection, use the purposive sampling method. The data collection methodology uses documentation with the type of data used, namely quantitative data. The method of analysis data, uses analysis, regression, linear, double, the results of this research show the value of R Square is 6.6%, this is means that the variables Cash Ratio, Roa, Asset Growth and Leverage can explain the relationship. Dividend Payout Ratio of 6.6%. The test results show that each independent variable in the study is Cash Ratio, Roa, Asset Growth and Leverage have no effect on the Dividend Payout Ratio.